Upaya Pencegahan Kecelakaan Kerja dengan Menerapkan Metode HIRARC di CV. SANTOSO JAYA - Kevin Reinaldo Santoso; Kriswanto Widiawan (Jurnal Titra, 2022)
CV. Santoso Jaya is a company engaged in logistics. The company never identified any hazards before, work accidents that often occur in the company are workers hit by goods when they are about to load goods, goods fall, and lifting positions are not ergonomic. Work accidents such as falling goods very often occur, within 1 month there can be more than 1 incident. Therefore, the purpose of making this final project is risk identification, risk assessment, and risk control (HIRARC) in CV. Santoso Jaya to minimize and eliminate the risks. The risk identification process is carried out on loading and unloading activities in the company's warehouse. Collecting data by observing and interviewing workers. After conducting observations and interviews, the authors then carried out risk identification, risk assessment, and risks control. The results from this research activity are that of the 13 sub-activities in central warehouse and branch warehouses, there are 2 sub-activities with a moderate risk rating, 6 with a significant risk rating, and 5 with a high risk rating. From the potential risks that have been identified, the researcher proposes risk control in the form of 1 type of elimination, 5 substitution, 5 design, 6 administration, and 6 PPE.